East Asian welfare regimes in transition : from Confucianism to globalisation / edited by Alan Walker and Chack-kie Wong. - Walker, Alan; Wong, Chack-kie (Policy Press, 2005)
This book explores the Chinese and South-East Asian welfare systems, providing an up-to-date assessment of their character and development. In particular, it examines their underlying assumptions and the impact of the processes of globalisation. As well as specific case studies, there is also a comparative analysis of Eastern and Western welfare states.